2017
DOI: 10.1016/j.chb.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Do you have anything to hide? Infidelity-related behaviors on social media sites and marital satisfaction

Abstract: Social media provides one route to behaviors that may be potentially harmful to romantic relationships, such as communicating with alternative partners, which can sometimes create relationship conflict, breakups, or divorce. Limited empirical evidence exists concerning social media infidelity-related behaviors and marital relationships. This study examined whether married/cohabiting individuals are using social media sites to engage in online infidelity-related behaviors and to what extent this related to rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 44 publications
(86 reference statements)
8
72
0
10
Order By: Relevance
“…The novelty of our study was the inclusion of measures of sexual satisfaction and emotional intimacy. In this sense, our research expands the work done by McDaniel et al [4], finding significant and inverse correlations between infidelity-related behaviors on social networks, sexual satisfaction, and emotional intimacy. Similarly, our study showed, like other studies [25,29], that emotional intimacy contributes more to a couple's well-being than sexual satisfaction.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The novelty of our study was the inclusion of measures of sexual satisfaction and emotional intimacy. In this sense, our research expands the work done by McDaniel et al [4], finding significant and inverse correlations between infidelity-related behaviors on social networks, sexual satisfaction, and emotional intimacy. Similarly, our study showed, like other studies [25,29], that emotional intimacy contributes more to a couple's well-being than sexual satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…Digital media worsens the complexity of formulating consistent and clear criteria for judging the infidelity behaviors that already exist outside digital platforms [8][9][10]. While we know that infidelity behaviors on social media also contain sexual and emotional variants-some of which are easily defined, such as flirting and intimate conversations-others may be more controversial, such as remotely chatting with someone, even with strangers [2][3][4]8,10]. On the other hand, researchers have detailed how certain behaviors that might be considered problematic are not perceived and described as such by certain groups.…”
Section: Introductionmentioning
confidence: 99%
“…Social media use often impacts a couple's life. In the United States studies show that 1 in 5 marriages are ruined for this reason (McDaniel et al, 2017). Either there is already a problem in the relationship and because people do not know how to deal with them, one or both partners resort to this mechanism which unfortunately creates a rupture even more dangerous and the gap between the two deepens even more or the accessibility of social media is the one that determines the problems, there is a clear connection between the two.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study noted that those with a household income lower than $30,000 USD were likely to argue about the time their partner spent online, or to find '...the online activity of their partner upsetting' (Pew Research Center, 2014 p. 16). Use of social media can cause conflict and drive dissatisfaction with relationships, as the platform provides a means for partners to meet others, leading to potential infidelity (McDaniel, Drouin, & Cravens, 2017). Dang-Pham, Pittayachawan, and Nkhoma (2015) point out that stalking and harassment are among the negative behaviours enabled by such social networking services.…”
Section: Relationship Satisfactionmentioning
confidence: 99%